Hepatitis B and D (Eurasian Research Bulletin, 2022)
In recent years, liver diseases have taken an important place among the main causes of premature disability and death of the population. Every year, more than 1 million people of the world are infected with liver diseases. Death due to viral hepatitis is increasing year by year. According to WHO data in 2015, viral hepatitis caused the death of 1.34 million people. 720,000 of them died from chronic liver diseases - liver cirrhosis and cancer, and 470,000 died from hepatocellular carcinoma (WHO, 2015y). In this article, the scientific work conducted on hepatitis B and D diseases on a global scale is studied, and their advantages over each other are explained in more detail